Potensi Tanaman Jagung dan Sangket (Basilicum Polystachyon) sebagai Perangkap Hama Pemakan Polong Kedelai - YIB, Marida Santi; Tengkano, Wedanimbi (Jurnal Penelitian Pertanian Tanaman Pangan, 2013)
Soybean pod feeder, Helicoverpa armigera is a major insect pest of soybean in Indonesia, where severe attacks can reduce yield significantly. This insect has a wide range of host plants. One of the Integrated Pest Management (IPM) components is using a trap crop. A study was conducted in the green house at the Indonesian Legumes and Tuber Crops Research Institute (ILETRI), Malang, from Januari to Februari 2011 to evaluate the potential use of musk basil plant as a trap for egg laying of the adult soybean pod feeder. The experiment was arranged in a complete randomized design with four replications. Maize plants of 54 and 57 days old, soybean plants of 35 days old, and musk basil plants were each inoculated with two pairs of adult insects for two days at 02.00 pm. The numbers of eggs laid by the insect on the plants were recorded at two days after infestation (DAI). The results showed that maize plants of 54 or 57 days old were the most preferred host for laying eggs, followed by the musk basil plant. The pest laid 63% of the eggs on 54 days old maize plants, 34% on the 57 days old maize plants, and only 1.8% on the musk basil plant. None was found laying egg on soybean plant. The insect preferred most maize stem (39.7%) to lay eggs, on maize leaves (35.2%), cob hair (23.1%), and on cob (1.3%). On musk basil plant, 70% of the eggs were laid on the fruits and 30% on the leaves. Maize plant was the best egg trap, while musk basil plant did not have a potential as trap plant for soybean pod feeder insect.